Enhancing German innovation through international trade in services - Bastian Krieger (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
The access to foreign knowledge via service imports fosters the success of innovations in Germany. The probability of firms in- troducing new or significantly improved products, services, or processes is more than twice as high for those that import knowl- edge services than for non-importers (68 per cent vs. 33 per cent). Furthermore, knowledge importers experience a greater av- erage percentage reduction in their unit costs due to new processes (three per cent vs. one per cent), and a larger revenue share from new products and services (18 per cent vs. eight per cent). Over the course of the previous decade, Germany witnessed a notable surge in the importation of knowledge services, with the value of such imports more than doubling from 16,949 million in 2010 to 46,392 million in 2022. Moreover, Germany's focus on the European Union as a trade partner significantly increased. The European Union's share of Germany's total imports of knowledge services rose from 35 per cent in 2010 to 44 per cent in 2019. This trend follows the proposed strategy of the German Federal Ministry of Education and Research (BMBF) to focus on a specific selection of countries as knowledge sources to enhance Germany's technological sovereignty and resilience to global challeng- es. However, to compensate for rising protectionism worldwide, trade barriers between Germany and its selected countries - in particular the EU single market - have the potential to be further reduced.
Keywords: 330; Innovation; trade in services; knowledge; service; import; Germany; Innovation; Dienstleistungshandel; Wissen; Dienstleistung; Import; Deutschland